2020
DOI: 10.1002/cam4.3042
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Pancreatic Ductal Adenocarcinoma—The Significance of Hispanic Ethnicity, Subgroup Analysis, and Treatment Facility on Clinical Outcomes

Abstract: Background Disparities exist among patients with pancreatic ductal adenocarcinoma (PDAC). Non‐White race is regarded as a negative predictor of expected treatment and overall survival. Data suggest that Academic Research Programs (ARP) provide better outcomes for minorities, but ethnic/minority outcomes are underreported. We hypothesize that outcomes among racially/ethnically diverse PDAC patients may be influenced by treatment facility. Methods The National Cancer Database was used to identify 170,327 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…In lung cancer, 5‐year survival is lower among Black patients than White patients 23 . In evaluating other GI malignancies, Black patients have been found to have worsened survival in gastric, colorectal, liver cancer, and the most common pancreatic cancer, pancreatic ductal adenocarcinoma 14,24–28 In our study, there were no significant differences in unadjusted or adjusted survival in NHW, NWB, and HW patients. A study using the NCDB to evaluate for racial/ethnic disparities in pancreatic ductal adenocarcinoma found that Hispanic patients, particularly those of Dominican descent, had improved survival 28 .…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In lung cancer, 5‐year survival is lower among Black patients than White patients 23 . In evaluating other GI malignancies, Black patients have been found to have worsened survival in gastric, colorectal, liver cancer, and the most common pancreatic cancer, pancreatic ductal adenocarcinoma 14,24–28 In our study, there were no significant differences in unadjusted or adjusted survival in NHW, NWB, and HW patients. A study using the NCDB to evaluate for racial/ethnic disparities in pancreatic ductal adenocarcinoma found that Hispanic patients, particularly those of Dominican descent, had improved survival 28 .…”
Section: Discussioncontrasting
confidence: 44%
“…Health disparities are known to underlie outcomes in nearly every malignancy 7–9 . Racial/ethnic and other socioeconomic disparities exist for patients with pancreatic ductal adenocarcinoma (PDAC), the most common type of pancreatic cancer 10–13 . Incidence and survival with PDAC vary by race/ethnicity, with Non‐Hispanic Black (NHB) patients having higher incidence and worse overall survival compared to Non‐Hispanic White (NHW) patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 In contrast, Hispanic patients diagnosed with pancreatic cancer have the longest median and overall survival when compared with other ethnic groups. 3 These disparities are not entirely accounted for by comorbidities, socioeconomic status, and access to high-quality health care alone, suggesting that biologic processes may be partially responsible. 4 Although it is critical to address the systemic injustices, institutional racism, and disadvantages faced by minority populations, ancestral differences in tumor biology cannot be overlooked.…”
mentioning
confidence: 99%
“…Although prior studies have demonstrated worse overall mortality, decreased access to high‐volume cancer centers, and decreased likelihood of receiving surgical and other multidisciplinary treatment modalities among Black patients, there is a paucity of literature regarding racial disparities in short‐term postoperative outcomes. It has been established that increased perioperative morbidity is associated with a decreased likelihood of receipt or completion of adjuvant therapy 2,9,39–42 . Therefore, this study sought to determine if differences in postoperative complications could explain previously observed racial disparities in receipt of multimodality adjuvant therapy and subsequent mortality.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have investigated the underlying etiologies of racial disparities in pancreatic cancer survival. It has been proposed that socioeconomic factors such as health insurance status, access to high‐volume cancer centers, referral to multi‐disciplinary cancer care, and refusal of indicated treatment may contribute to worse long‐term outcomes among Black patients 14,39,40,44,44,45 . In a recent study of over 280,000 patients with resected pancreatic cancer identified within the NCDB, Black race was associated with overall worse survival.…”
Section: Discussionmentioning
confidence: 99%